The Students' Difficulties In Speaking At The Tenth Grade Of SMA Negeri 1 Sine In 2014/2015 Academic Year - Pradya Afisa, Sheila Yolanda, Drs. Djoko Srijono, M.Hum, Dra. Muamaroh, M.Hum, Ph.D (2015)
This study aims at describing the students' difficulties in speaking English at SMA Negeri 1 Sine. Besides, the researcher also wants to know what the students' difficulties in speaking English and what factors contribute to the difficulties in speaking English for the students. The type of the research is descriptive research. The subject of this research is the English teacher and the tenth grade students of SMA N 1 SINE. The object of this research is to describe the students' difficulties in speaking English and to describe the factors that contribute the difficulties in speaking English by the students. The method of collecting data are observation, recording, and interview. The data are taken from the subject of the research in the form of teaching learning process, interview and recording. The research finding shows that the students difficulties in speaking English are: (a) the student's low vocabulary mastery resulted from their limited knowledge of meaning vocabulary had led them difficulties in understanding the conversation. (b) the students had difficulties in pronouncing certain words because, English words are different between pronunciation and writing. (c) the students were still confused in arranging words. Then, there were still some mistakes in their grammar. (d) the students were often afraid of speaking English because they were worried of making mistakes. They were unconfident and nervous when the teachers were asking them. Second, factors that contribute to the difficulties in speaking English are: the quantity of the students in learning speaking English and student's psychological factors.